Effect of glucose replacement and low intensity exercise on postprandial lipaemia - Pang, Joel Wen Jie (2015)
Exercise is an effective method of reducing postprandial lipaemia (PPL). However, it remains uncertain whether the attenuation of exercise-induced PPL is determined by replacement of exercise-induced energy deficit or substrate utilized. This study investigated glucose substrate replacement of exercise-induced fat deficit on PPL. We hypothesize that PPL will be highest in the CON, EX-G, EX trial in a decreasing manner. Four young, healthy, sedentary, Asian males (Age: 23.25 (0.50)y; BMI: 21.26 (1.46)kg/m2; maximum oxygen consumption: 2.25 (0.28)L/min; Body fat %: 16.95 (2.06)%) completed three 2-day trials in a randomized repeated design. Evening of day-1, participants either rested (CON) or walked at 31.28 (2.93)%VO2max until 302.04 (28.15)kcal was expanded, with (EX-G) or without (EX) the consumption of a 330 kcal glucose following exercise. Morning of day-2, venous blood samples were collected before and 5h postprandially, after consumption of an oral fat tolerance test (1.21g fat, 0.62g carbohydrate, 0.29g protein, consisting of ~14.48kcal/kg body weight). Plasma extracted was analyzed for triglyceride concentrations using a dry-chemical analyzer. No significant differences were observed amongst the trials for the incremental area under the TG concentration-time curve (p = .143), main effect on trial (p = .236) and trial x time interaction (p = .292). However, tendencies of PPL reductions of 30.63% with small-moderate effect sizes (d = -0.45) were observed in EX-G trial compared to CON. Although no statistical significant differences were observed, reductions in PPL concentrations was still observed despite glucose replacement. Future studies should examine the specific mechanisms underlying the substrate deficits